Ovid's changing worlds English metamorphoses, 1567-1632 - Lyne, Raphael (Oxford University Press, 2001)
This text looks at the four most important English imitations of Ovid's Metamorphoses in the English Renaissance. It sheds new light on dealings with the classics in the period and shows that the emergence of English literature was a complex process.